Targeting the activated allosteric conformation of the endothelin receptor B in melanoma with an antibody-drug conjugate: mechanisms and therapeutic efficacy - Amaury Herbet; Marie Hautière; Frédéric Jean-Alphonse; Delphine Vivier; Christophe Leboeuf; Narciso Costa; Aloïse Mabondzo; Guilhem Bousquet; Franck Denat; Eric Reiter; Didier Boquet (BJC Reports)
Abstract Background Endothelin 1 receptors are one of the drivers of tumor progression in many cancers. Inhibition of their signaling pathways with antagonist drugs has been the subject of numerous clinical trials, but the results have not met expectations probably due to the high endothelin concentrations in the tumor microenvironment and their unusually high affinity for their receptors. Methods We previously reported the rendomab B49 antibody (RB49) exhibiting a preferential affinity for the activated conformation of human endothelin B receptor (ETB), not displaced by high endothelin levels, and without any pharmacological properties that could inhibit the division of melanoma cells. In this context, we have developed xiRB49-MMAE, a chimeric antibody-drug conjugated (ADC) to monomethyl auristatin E. We have characterized its physicochemical properties, studied its binding mechanisms, and evaluated its therapeutic potential in a preclinical model. Immunohistochemical analysis of metastatic melanoma lymph nodes evaluated RB49 as a diagnostic tool for patient stratification. Results xiRB49-MMAE showed high efficacy against melanoma cells and ETB + xenograft tumor models. IHC studies indicated that 100% of melanoma patient lymph node biopsies were RB49-positive. Conclusions xiRB49-MMAE is a promising drug candidate for clinical trials in ETB + tumors. RB49 could be used as a diagnostic tool for patient stratification.